Description of new species of Phanodermopsis (Enoplida, Phanodermatidae) with key to genera of family Phanodermatidae and pictorial key to Phanodermopsis species - Zograf, Julia K.; Trebukhova, Yulia A.; Pavlyuk, Olga N. (Zootaxa, 2015)
A new representative of the family Phanodermatidae, Phanodermopsis nana sp. n., is described. The new species is found in the Sea of Japan and characterized by its small body size, long anterior sensilla and short tail. The new species differs from P. ingrami in body length ( 7000 µm in P. ingrami vs 3000 µm in P. nana sp. n.). The De Man’s ratios (a, b, c) are smaller in P. nana sp. n. and the outer labial setae are longer (1 corresponding body diameter) than in P. ingrami (1/2 corresponding body diameter). The vulva is more posterior in P. ingrami (V% = 58–61%) than in P. nana sp. n. (V% = 51–58%). A dichotomous key to the 9 valid genera of Phanodermatidae and a pictorial key to species of Phanodermopsis are provided. The length of the spicules is proposed as the main differentiating feature for distinguishing Phanodermopsis and Crenopharynx species. Phanodermopsis longisetae Chitwood, 1936 which has extremely long spicules (5.2 anal body diameters) is transferred to the genus Crenopharynx.